OPTIMALISASI MODEL SISTEM INFORMASI PENGELOLAAN ARSIP ELEKTRONIK PADA PEMERINTAH KABUPATEN SRAGEN - Ardiansyah, Moch. Arfian; Winarno, Wing Wahyu; Nasiri, Asro (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2020)
Electronic records management information system in the Sragen regency government (SIALEK) is an information system that functions to store records in digital form such as letter, photo and other archives. SIALEK can be accessed by each regional apparatus organization (OPD) to store the files of each OPD. Data stored at this time is only for storage. For several years, the electronic archive management information system in Sragen regency government has been very minimal in operation. The reason is the decline in performance on the information system. The decrease in performance is due to the data structure in the database owned by SIALEK that is not well organized and when there is already a lot of data, so the performance decreases. This research aims to provide a proposal for modeling a new database to improve the performance of SIALEK and modeling a new information system to maximize the function of SIALEK to provide information about archiving to the Sragen district government. By changing the database to PostgreSQL and normalizing the table structure. The results showed that there were differences in performance in the form of fast response time and smaller database table sizes after normalizing and moving databases. The modeling of the new system makes SIALEK not only a storage medium but also produces some information in the form of a dashboard on the system that is useful for providing information related to the archives of the Sragen district government.